Reflection of the Thought of Defense in Kurdish Proverbs - Sazan Jawhar Hamaghareb (Zanco Journal of Humanity Sciences)
This research is entitled (Reflection of the Thought of Defense in Kurdish Proverbs), an opportunity to become more familiar with the thoughts and ideas about defense and encouragement to resistance, rebellion, unity and fearlessness, which are reflected in different expressions in Kurdish proverbs. The paper consists of an introduction and two parts. The first part is theoretical and consists of two topics. The first topic is devoted to explaining the concepts and terms necessary to understand the concept of defense such as defense terms, defense concepts in politics, defense literature, the role of language in defense literature, and the formation of defensive characteristics in Kurdish literature. The second topic presents the definition and characteristics of proverbs and the appearance and content of proverbs of the ancestors. What is related to the second part is practical and an attempt has been made to distinguish the various expressions of the method of defense within the proverbs and classify them under their own titles. Finally, the results of the study and a list of sources were presented, and a summary of the study was presented in both Arabic and English.